The Consequences of Social Media on our Mental Health are Worrisome - Amado Rodríguez, Juan Sebastián (Universidad Pedagógica y Tecnológica de Colombia, 2022)
In our current society, all of us are using social media for different purposes, such ascommunication, work, entertainment, etc. However, those interactions are affecting our mental healthevery day, not only during the time we spend in front of a screen but because we are constantly gettinga lot of different information. That kind of information varies from seeing what our friends are doingto watching YouTube videos non-stop. This problem is affecting not only teenagers but also adults.